Malala, a brave girl from Pakistan/Iqbal, a brave boy from Pakistan - Winter, Jeanette (Beach Lane Books, 2014)
"Two stories of bravery in one beautiful book! Meet two brave young heroes of Pakistan who stood up for the right to freedom and education in this inspirational nonfiction picture book from acclaimed author-illustrator Jeanette Winter. One country: Pakistan. Two children: Iqbal Masih and Malala Yousafzai. Each was unafraid to speak out. He, against inhumane child slavery in the carpet trade. She, for the right of girls to attend school. Both were shot by those who disagreed with them--he in 1995, she in 2012. Iqbal was killed instantly; Malala miraculously survived and continues to speak out around the world. The stories of these two courageous children whose bravery transcended their youth are an inspiration to all"--